2022
DOI: 10.1002/jobm.202200216
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community composition and soil metabolism in the coexisting Cordyceps militaris and Ophiocordyceps highlandensis

Abstract: Cordyceps sensu lato is a complex fungus‐larva symbiote, and its distribution is affected by the geography, climate, soil environment, and cohabitating microorganisms. However, despite the fact Cordyceps militaris and Ophiocordyceps highlandensis are different species, they coexist in the Pinus armandi forest of Dashao in Songming County, Yunnan, China. We explored the microbial compositions and soil metabolism inhabited by C. militaris and O. highlandensis using high‐throughput sequencing and nontargeted meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…On the other hand, the maximum Simpson index was observed in O. indica associated isolates in the year 2019 (0.929), followed by 2016 (0.889) and 2017 (0.667) (Table 3a, b). Furthermore, the Chao-1 index for species richness also showed a similar trend, with the highest richness in the year 2019 (55), followed by 2016 (21) and 2017 (10) in soil isolates. Whereas, in the case of O. indica isolates, the highest richness was governed in the year 2019 (105), followed by 2016 (45) and 2017 (6).…”
Section: Associated Fungi Alpha-diversitymentioning
confidence: 62%
See 3 more Smart Citations
“…On the other hand, the maximum Simpson index was observed in O. indica associated isolates in the year 2019 (0.929), followed by 2016 (0.889) and 2017 (0.667) (Table 3a, b). Furthermore, the Chao-1 index for species richness also showed a similar trend, with the highest richness in the year 2019 (55), followed by 2016 (21) and 2017 (10) in soil isolates. Whereas, in the case of O. indica isolates, the highest richness was governed in the year 2019 (105), followed by 2016 (45) and 2017 (6).…”
Section: Associated Fungi Alpha-diversitymentioning
confidence: 62%
“…It is worth noting that extensive studies have been reported on the associated fungal communities with O. sinensis. However, in recent years, microbial associations with respect to Cordyceps militaris and O. highlandensis have also been studied [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations